Canine as a Comparative and Translational Model for Human Mammary Tumor - Kwon, Jee Young; Moskwa, Nicholas; Kang, Wonyoung; Fan, Timothy M.; Lee, Charles (Journal of breast cancer, 2023)
Despite the advances in research and treatment of human breast cancer, its incidence rate continues to increase by 0.5% per year, and the discovery of novel therapeutic strategies for specific subtypes of human breast cancer remains challenging. Traditional laboratory mouse models have contributed tremendously to human breast cancer research. However, mice do not develop tumors spontaneously; consequently, genetically engineered mouse models or patient-derived xenograft models are often relied upon for more sophisticated human breast cancer studies. Since human breast cancer develops spontaneously, there is a need for alternative, yet complementary, models that can better recapitulate the features of human breast cancer to better understand the molecular and clinical complexities of the disease in developing new therapeutic strategies. Canine mammary tumors are one such alternative model that share features with human breast cancer, including prevalence rate, subtype classification, treatment, and mutational profiles, all of which are described in this review.